Miocene evolution of source to sink in the Xihu Depression: evidence from Diaoyu island fold-uplift belt provenance in the East China Sea - Zhiyi Tang; Donghui Jiang; Kun Li; Feng Wu; Beichen Chen; Xin Dong; Xinong Xie (Journal of Asian Earth Sciences, 2026)

Highly efficient single-layer color-tunable QLEDs enables by the real-time interface exciplex modulation with AgInZnS QDs - Tianjun Hu; Xiuting Wu; Qingsong Shan; Xingxing Duan; Xiaoyue Cai; Mengjin Huang; Junhui Dai; Hong Zhong; Beichen Yuan; Hengyang Xiang; Linxiang Yang; Qiangyu Dai; et al. (Science Bulletin, 2026)

Economic optimization scheduling of combined cooling, heat, and power systems utilizing a multi-strategy enhanced PSO algorithm - Beichen Chen; Haoyuan Lv; Wenpeng Hong; Qingyu Su; Jian Li (Swarm and Evolutionary Computation, 2026)

Research on the damage laws and failure characteristics of sandstone in coal seam roofs under different rich-water conditions - Yu Chen; Man Wang; Dongming Zhang; Beichen Yu; Ziyang Xiong; Wenzhuo Li (Bulletin of Engineering Geology and the Environment, 2026)

In-situ passivation of Cu and Zn in dyeing sludge incineration ash: Neglected role of the sulfur cycle - Beichen Du; Yuting He; Qinyuan Zhang; Jianran Ye; Xiao Hu; Chuqi Ye; Yuchi Chen; Siwei Liu; Jia Hu; Teng Wang (Journal of Environmental Chemical Engineering, 2025)

Integrative analysis identifies FERMT3 as a key regulator of metabolic reprogramming in keloid scarring and metabolic syndrome - Qian Lin; Beichen Cai; Feng Dong; Ruonan Ke; Xiuying Shan; Xuejun Ni; Lu Chen; Chuanshu Cai; Biao Wang (Functional & Integrative Genomics, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Late Miocene carbonate-system evolution in the Xisha area, northern South China Sea - Feng Wu; Zhimin Jian; Xinong Xie; Giovanni Coletti; Youhua Zhu; Zhilei Shang; Beichen Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Characterizing a complex buildup in the Pearl River Mouth Basin of the northern South China Sea: an interplay of carbonates and igneous rocks - Beichen Chen; Leyi Xu; Baojun Liu; Lili Zhang; Dong Xiao; Ya Gao; Feng Wu; Xueqi Yang; Yaming Zou; Yongkun Ma; Yinglin Zhang (Frontiers in Marine Science, 2025)
Volcanic mounds and carbonate buildups share similar geometries, making their differentiation in seismic data a significant challenge. This challenge is further compounded in complex buildups composed of both multi-stage developed igneous rocks and biogenic carbonates. To address this gap, this study investigates a mixed carbonate-igneous buildup at the central of the Baiyun Sag in the northern South China Sea. By analyzing the lithofacies of the carbonates and igneous rocks, the morphological features and spatial distribution patterns corresponding to these sedimentary and volcanic facies were identified. Well-to-seismic calibration was used to delineate the stratigraphic units, and typical seismic profiles of the buildup were analyzed. Eight distinct seismic facies were identified for carbonates and igneous rocks. The evolution of the buildup is divided into three stages: (1) volcanic eruptions and carbonates development, (2) overflowing magma and reef shoal deposits, and (3) reef-bank deposition accompanied by igneous intrusion. We propose that volcanic rocks can be distinguished from carbonates by the temporal and spatial coupling of typical features: (a) surface volcanic rocks and subsurface intrusive bodies are inseparable, with igneous rocks identifiable through faults and volcanic conduits; (b) carbonates typically display symmetrical structures on both sides of the highland and exhibit better stratification away from igneous activity; (c) carbonates generally show a convex clinoform and steep slope at the platform margin, while volcanic mounds exhibit concave gentle slopes. Furthermore, the analysis of high-quality reservoir development within the complex buildups is instrumental for advancing oil and gas exploration in volcanic seamounts and carbonate buildups.

A web-based tool for watershed delineation considering lakes and reservoirs - Beichen Zhang; Junzhi Liu; Bin Zhang; Dawei Xiao; Min Chen (Environmental Modelling & Software, 2025)

Fast preparing bioelectrode with conductive bioink for nitrite detection in high sensitivity and stability - Shaoan Cheng; Hua Chen; Huahua Li; Longxin Li; Yi Lu; Beichen Jin; Xinyuan He (Environmental Research, 2024)

Sequence stratigraphic analysis of the late Permian Changhsingian platform marginal reef, Western Hubei, South China - Beichen Chen; Feng Wu; Xinong Xie; Ya Gao; Wang Xiao; Zhiyi Tang (Frontiers in Marine Science, 2024)
This study presents a comprehensive analysis of the late Permian platform marginal reefs in the Sichuan Basin, focusing on reefal lithofacies and sequence stratigraphic patterns. Field outcrop observations and rock sample analyses from the Jiantianba reef were conducted to establish an evolution model of sponge reef development and spatial distribution. Four stages of marginal carbonate platform were documented: open platform, gently sloping reef, steeply sloping reef, and reef bank system. Distinct lithofacies were identified in these stages, reflecting different depositional environments and growth rates. The gently sloping reef was composed of filled skeleton framestone, filled skeleton bafflestone, and micrite organism limestone, indicating limited reef-building capacity. In contrast, the lithofacies of steeply sloping reefs were composed of open skeleton framestone, open skeleton bafflestone, binding skeleton bafflestone, and benthic organism bindstone, indicating stronger reef-building ability. Based on depositional features and carbon isotopic trends, the reef strata were divided into two sequences. Sequence 1 corresponds to the formation of unit 1, and sequence 2 can be further divided into units 2 and 3. In unit 1, reefs developed in a relatively deeper-water setting. It was characterized by rich micrite limestone, forming a gentle margin. Unit 2 witnessed reef development in shallower waters. Early marine cementation and microbial clots were prevalent, contributing to form a steep margin. In the early stage of unit 3, reefs primarily developed in a tidal-controlled environment. Subsequently, reef strata experienced a transition to a wave-influenced environment, leading to the formation of a reef bank system. In general, sequence 1 mainly formed in a heterozoan-dominated factory, and reefs contributed to a relatively gently sloping platform margin. In contrast, sequence 2 formed in a photozoan-dominated factory, and reefs contributed to a relatively steeply sloping platform margin.

Self-supporting three-dimensional CuNi–Sb–SnO2 anode with ultra-long service life for efficient removal of antibiotics in wastewater - Beichen Jin; Shaoan Cheng; Longxin Li; Huahua Li; Yuxiang Zhou; Hua Chen (Chemosphere, 2024)

Triggering dual-mode dynamic optical responses by anchoring carbon dots on MnO2 hollow spheres - Sisi Li; Yajing Cai; Jiaying Situ; Biwen Wang; Beichen Ying; Jin He; Zhao-Qing Liu; Jianle Zhuang; Yibo Chen (Chemical Engineering Journal, 2024)

Holocene sedimentary distribution and morphological characteristics reworked by East Asian monsoon dynamics in the Mekong River shelf, South Vietnam - Xiao Wang; Wenyan Zhang; Xinong Xie; Hui Chen; Beichen Chen (Estuarine, Coastal and Shelf Science, 2024)

Acoustic emission noise reduction: A case of a uniaxial compression test of gypsum-like rock - Chongyang Wang; Dongming Zhang; Ziyang Xiong; Beichen Yu; Xiaolei Wang; Fake Ren; Yu Chen (International Journal of Rock Mechanics and Mining Sciences, 2024)

High-sensitive determination of tetracycline antibiotics adsorbed on microplastics in mariculture water using pre-COF/monolith composite-based in-tube solid phase microextraction on-line coupled to HPLC-MS/MS - Jinling Pang; Hongzhe Chen; Huige Guo; Kunning Lin; Shuyuan Huang; Beichen Lin; Yuanbiao Zhang (Journal of Hazardous Materials, 2024)

Design and Experimental Study of 50 kW Ocean Thermal Energy Conversion Test Platform Based on Organic Rankine Cycle - Beichen Lu; Yanjun Liu; Xiaoyu Zhai; Li Zhang; Yun Chen (Journal of Marine Science and Engineering, 2024)
In recent years, clean and renewable energy sources have received much attention to balance the contradiction between resource needs and environmental sustainability. Among them, ocean thermal energy conversion (OTEC), which consists of surface warm seawater and deep cold seawater, can rely on thermal cycling to generate electricity and has great potential in alleviating the energy crisis. In this paper, the design and experiment study of a 50 kW OTEC platform is proposed. Thermodynamic modeling, calculation, optimization, and engineering calibration of the system were carried out, and the thermal efficiency reached 2.63% to meet the power generation demand. Experiments were also carried out by using a heat pump unit to simulate hot and cold seawater environments, and data on the stable operation of the system were obtained, with the grid-connected power reaching 47.5 kW and a thermal efficiency of 2.46%. The accuracy of the design scheme is verified, and the theoretical basis and data support are provided for the practical development and application of ocean thermal energy conversion.

Quaternary evolution of the Meiji Atoll (Mischief Reef) in the southern South China Sea - Feng Wu; Xinong Xie; Wen Yan; Youhua Zhu; Beichen Chen; Jianuo Chen; Mo Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Coralline algal and foraminiferal records of the Pliocene paleoclimatic conditions and water-depth changes in the northern South China Sea - Feng Wu; Xinong Xie; Giovanni Coletti; Youhua Zhu; Beichen Chen; Zhilei Shang (Marine and Petroleum Geology, 2023)

Molecular level insight into the different interaction intensity between microplastics and aromatic hydrocarbon in pure water and seawater - Wenjin Liu; Huan Tang; Beichen Yang; Chenyang Li; Ying Chen; Tinglin Huang (Science of The Total Environment, 2023)

An online participatory system for SWMM-based flood modeling and simulation - Beichen Zhang; Min Chen; Zaiyang Ma; Zhuo Zhang; Songshan Yue; Dawei Xiao; Zhiyi Zhu; Yongning Wen; Guonian Lü (Environmental Science and Pollution Research, 2022)

Sequence stratigraphy of the Late Oligocene carbonate system on the Xisha Islands in the South China Sea - Feng Wu; Xinong Xie; Youhua Zhu; Beichen Chen; Zhilei Shang (International Journal of Earth Sciences, 2021)